The Potential at Phytochemical Compounds from the Indonesian Kalimantan Plant as Covid-19 Immunomodulators - Chairana Fadya; Ahmad Luthfi Haqiqi; Annisa Miladdiannur; Monika Yati; Ummu Salamah Az Zahra; Neni Oktiyani; Wahdah Norsiah (Tropical Health and Medical Research, 2022)
Herbal plants are alternative medicine and immunity boosters related to the Covid-19 pandemic. Typical Kalimantan plants that have the potential are dayak onion (Eleutherine americana Merr.), karamunting (Rhodomyrtus tematosa (Aiton) Hassk), pasak bumi (Eurycoma longifolia Jack), and tigaron (Crataeva adansonii DC). This study aims to determine the potential of phytochemical compounds from Indonesian Kalimantan plants as Covid-19 immunomodulators. Descriptive research with cross-sectional study design by testing the typical plants of Kalimantan, which were extracted first through the maceration method and then carried out qualitative and quantitative phytochemical tests. Qualitative and quantitative results showed that the four positive plants contained phytochemical alkaloids, flavonoids, saponins, and tannins in certain levels. Quantitative results on dayak onion (Eleutherine americana Merr.) obtained alkaloid content; flavonoids; saponins; tannins were 74.540%; 22.125 mg/mL; 58.350%; 0.342 mg/mL. karamunting fruit (Rhodomyrtus tematosa (Aiton) Hassk) 72.815%; 20,500 mg/mL; 78.225%; 0.541 mg/mL. pasak bumi (Eurycoma longifolia Jack) 68.575%; 12,250 mg/mL; 53.930%; 0.383 mg/mL; and tigaron (Crataeva adansonii DC) 82.330%; 40,750 mg/mL; 75.395%; 0.609 mg/mL. The four phytochemical compounds have the potential as Covid-19 immunomodulators. This study concludes that the typical plant from Kalimantan that has been studied has the potential. This research can be continued by testing the effectiveness of phytochemicals as Covid-19 immunomodulators in experimental animals.